High-thermal-conductivity polyurethane potting adhesive and preparation method thereof
Patent Information
- Application Number
- CN202310392625.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-13
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-04-13
AI Technical Summary
[0004]前者添加的金属化合物(球形氧化铝、片状氧化铝、氢氧化铝、氢氧化镁和氮化铝中的一种或多种)为Lewis碱或者Lewis酸,由于Lewis酸碱能催化加快聚氨酯的水解速度,极大地缩减了聚氨酯的耐水性,因此这种添加上述化合物制备的聚氨酯灌封胶耐湿性较差
[0027] Preferably, in step (1), the temperature for heating and vacuum dehydration is 80-100℃ and the time is 3-8h, and the temperature for heating reaction is 30-50℃ and the time is 4-9h; in step (2), the temperature for heating and ripening is 40-80℃ and the time is 6-24h.
Smart Images

Figure CN117821005B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane technology, and in particular to a high thermal conductivity polyurethane potting compound and its preparation method. Background Technology
[0002] To ensure the normal and stable use of electronic components, many parts require potting to secure them and protect them from environmental influences. Polyurethane potting compounds are widely used due to their low hardness, moderate strength, good elasticity, water resistance, mildew resistance, excellent electrical insulation and flame retardancy, non-corrosiveness to electrical components, good adhesion to metals such as steel, aluminum, copper, and tin, as well as materials such as rubber, plastics, and wood, and their moderate price. Polyurethane potting compounds are typically produced by the condensation polymerization of isocyanates and liquid polyethers or polyester glycols.
[0003] To ensure the operational stability of electronic components, higher requirements are placed on the thermal conductivity of polyurethane potting compounds. Reported thermally conductive polyurethane potting compounds mainly achieve this by adding one or more thermally conductive materials to the polyurethane, such as spherical alumina, flake alumina, aluminum hydroxide, magnesium hydroxide, and aluminum nitride (e.g., public patents CN115651596A, CN115322734A, CN115572363A, CN114316882A); or by adding inorganic thermally conductive materials such as silicon nitride, silicon carbide, and boron nitride (e.g., public patents CN112608708A, CN115160972A).
[0004] The former type adds metal compounds (one or more of spherical alumina, lamellar alumina, aluminum hydroxide, magnesium hydroxide, and aluminum nitride) that are Lewis bases or Lewis acids. Since Lewis acids and bases can catalyze and accelerate the hydrolysis of polyurethane, they significantly reduce the water resistance of polyurethane. Therefore, polyurethane potting compounds prepared with these added compounds have poor moisture resistance. The latter type adds nitrides, etc., which greatly improve the thermal conductivity of polyurethane potting compounds. However, these inorganic substances have poor compatibility with polyurethane. Under prolonged high temperatures, these inorganic substances face the problem of dissolution, leading to a significant decrease in thermal conductivity over time. The adhesive strength of the polyurethane potting compound also decreases, and cracking may even occur. Summary of the Invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a high thermal conductivity polyurethane potting compound and its preparation method. Under the premise of avoiding the catalytic effect on polyurethane and overcoming the dissolution of thermally conductive fillers, the polyurethane potting compound is endowed with better thermal conductivity and bonding strength, thereby solving the problems of heat dissipation and device stability after electronic device potting.
[0006] This invention proposes a high thermal conductivity polyurethane potting compound, comprising component A and component B; wherein,
[0007] Component A comprises the following raw materials in parts by weight: 60-100 parts of polyol, 5-15 parts of chain extender, 5-15 parts of plasticizer, 0.01-0.05 parts of catalyst, 0.01-0.05 parts of defoamer, and 15-30 parts of mesophase pitch-based foamed carbon powder.
[0008] Component B comprises the following raw materials in parts by weight: 60-100 parts isocyanate and 10-25 parts polymer polyol.
[0009] Preferably, the mass ratio of component A to component B is 1-4:1.
[0010] Preferably, the polyol is a vegetable oil polyol and / or a polymer polyol;
[0011] Preferably, the vegetable oil polyol is at least one of castor oil, palm oil, or soybean oil; and the polymer polyol is at least one of polypropylene glycol, polyglycerol, or hydroxyl-terminated polybutadiene.
[0012] Preferably, the chain extender is a small molecule diol;
[0013] Preferably, the small molecule diol is at least one of 1,4-butanediol, diethylene glycol, 1,3-propanediol, or neopentyl glycol.
[0014] Preferably, the plasticizer is at least one of dibutyl terephthalate, didecyl terephthalate, dimethyl adipate, or didecyl adipate.
[0015] Preferably, the catalyst is at least one of dibutyltin dilaurate, bismuth neodecanoate, or zinc neodecanoate;
[0016] Preferably, the defoamer is at least one of BYK1794, polymeric defoamer BYK1790, or silicone defoamer BYK066N.
[0017] Preferably, the particle size of the mesophase pitch-based foamed carbon powder is 100-300 mesh;
[0018] In this invention, the mesophase pitch-based foamed carbon powder is used as a thermally conductive filler. Its particle size is controlled so that it can be effectively compounded in polyurethane and the thermal penetration threshold is reduced, thus taking into account both high thermal conductivity and processing performance, thereby successfully preparing a polyurethane potting compound with high thermal conductivity and insulation.
[0019] Preferably, the mesophase pitch-based foamed carbon powder is an amino-functionalized mesophase pitch-based foamed carbon powder. This amino-functionalized mesophase pitch-based foamed carbon powder is obtained by hydrolyzing mesophase pitch-based foamed carbon powder with tetraethyl orthosilicate to obtain a composite material of mesophase pitch-based foamed carbon / SiO2. After coupling the composite material of mesophase pitch-based foamed carbon / SiO2 with an aminosilane coupling agent, the amino-functionalized mesophase pitch-based foamed carbon powder is obtained.
[0020] Preferably, the aminosilane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, or 3-(2-aminoethylamino)propyltrimethoxysilane.
[0021] In this invention, tetraethyl orthosilicate and mesophase pitch-based foamed carbon are used as raw materials. After hydrolysis, tetraethyl orthosilicate generates SiO2, which is distributed in the surface pores of the mesophase pitch-based foamed carbon. On the one hand, it can act as a thermal bridge, connecting the separated mesophase pitch-based foamed carbon to construct a thermally conductive network with high connectivity. On the other hand, it can undergo a coupling and grafting reaction with an aminosilane coupling agent to obtain mesophase pitch-based foamed carbon powder with amino functional groups. Since amino groups can react with isocyanates and participate in the synthesis of polyurethane, the mesophase pitch-based foamed carbon powder and polyurethane form molecular bonds, which can further enhance the compatibility between the mesophase pitch-based foamed carbon powder and polyurethane, ultimately obtaining a polyurethane potting compound with better thermal conductivity.
[0022] Preferably, the isocyanate is at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, or terephthalic diisocyanate.
[0023] Preferably, the polymeric polyol is at least one of hydroxyl-terminated polybutadiene, polypropylene glycol, polycarbonate diol, poly(1,4-butanediol adipate) diol, or poly(ethylene adipate) diol.
[0024] This invention also proposes a method for preparing a high thermal conductivity polyurethane potting compound, comprising the following steps:
[0025] (1) Mix 60-100 parts of polyol, 5-15 parts of chain extender, 5-15 parts of plasticizer, 0.1-0.5 parts of catalyst, 0.01-0.05 parts of defoamer and 15-30 parts of mesophase pitch-based foamed carbon powder evenly by weight, and heat and dehydrate under vacuum to obtain component A; mix 60-100 parts of isocyanate and 10-25 parts of polymer polyol evenly by weight, and heat and react to obtain component B;
[0026] (2) Mix component A and component B evenly, and heat to cure, to obtain the high thermal conductivity polyurethane potting compound.
[0027] Preferably, in step (1), the temperature for heating and vacuum dehydration is 80-100℃ and the time is 3-8h, and the temperature for heating reaction is 30-50℃ and the time is 4-9h; in step (2), the temperature for heating and ripening is 40-80℃ and the time is 6-24h.
[0028] The present invention proposes a high thermal conductivity polyurethane potting compound and its preparation method. By adding mesophase pitch-based foamed carbon powder to polyurethane, the mesophase pitch-based foamed carbon is a porous carbon material composed of interconnected bubble walls formed by central bubbles and surrounding regularly arranged carbon-graphite sheet structures. Therefore, on the one hand, the mesophase pitch-based foamed carbon powder is a neutral material and has no catalytic effect on the decomposition of polyurethane; on the other hand, the mesophase pitch-based foamed carbon powder contains CH bonds, which form hydrogen bonds with polyurethane without causing dissolution problems. At the same time, the mesophase pitch-based foamed carbon contains a large number of pores, and after some of the pores are filled by polyurethane, the two are integrated, and there will be no phenomenon of long-term high-temperature dissolution or phase separation.
[0029] Meanwhile, the mesophase pitch-based foamed carbon thermally conductive filler used in this invention is common and inexpensive, and the process is simple and efficient. The two-component polyurethane structural adhesive prepared therefrom has a thermal conductivity as high as 3.23 W / (mK) and also has high bonding strength to the substrate (greater than 5 MPa). These characteristics make it have broad application prospects and practical value in the field of electronic packaging. Attached Figure Description
[0030] Figure 1 This is an appearance diagram of the mesophase pitch-based foamed carbon powder used in Example 1. Detailed Implementation
[0031] The present invention will now be described in detail through specific embodiments. However, these embodiments are clearly provided for illustrative purposes and are not intended to limit the scope of the present invention.
[0032] Example 1
[0033] A high thermal conductivity polyurethane potting compound is prepared by the following method:
[0034] (1) Preparation of component A:
[0035] 80 parts by weight of hydroxyl-terminated polybutadiene (molecular weight 2750, hydroxyl value 0.75 mmol / g), 12.5 parts of 1,4-butanediol, 12.5 parts of dimethyl adipate, 0.01 parts of dibutyltin dilaurate, 0.015 parts of organosilicon defoamer BYK 066N, and 28.5 parts of mesophase pitch-based foamed carbon powder (particle size 200 mesh) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 90°C and dehydrated and degassed under vacuum for 5 hours to obtain component A.
[0036] (2) Preparation of component B:
[0037] 90 parts by weight of diphenylmethane diisocyanate (MDI-50) and 10 parts by weight of hydroxyl-terminated polybutadiene (molecular weight 2750, hydroxyl value 0.75mmol / g) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 40°C and reacted for 5 hours before degassing to obtain component B.
[0038] (3) Preparation of high thermal conductivity polyurethane potting compound:
[0039] During potting, component A and component B are mixed evenly at a mass ratio of 3:1 and cured at 60°C for 6-12 hours to obtain the high thermal conductivity polyurethane potting compound.
[0040] Example 2
[0041] A high thermal conductivity polyurethane potting compound is prepared by the following method:
[0042] (1) Preparation of component A:
[0043] 60 parts by weight of castor oil (hydroxyl equivalent of 345, average hydroxyl functionality of 2.7), 15 parts of diethylene glycol, 5 parts of dibutyl terephthalate, 0.03 parts of bismuth neodecanoate, 0.01 parts of organosilicon defoamer BYK 066N, and 30 parts of mesophase pitch-based foamed carbon powder (particle size of 200 mesh) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 80°C and dehydrated and degassed under vacuum for 8 hours to obtain component A.
[0044] (2) Preparation of component B:
[0045] 60 parts by weight of hexamethylene diisocyanate and 25 parts by weight of hydroxyl-terminated polybutadiene (molecular weight 2750, hydroxyl value 0.75mmol / g) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 30°C and reacted for 9 hours before degassing to obtain component B.
[0046] (3) Preparation of high thermal conductivity polyurethane potting compound:
[0047] During potting, component A and component B are mixed evenly at a mass ratio of 2:1 and cured at 40°C for 24 hours to obtain the high thermal conductivity polyurethane potting compound.
[0048] Example 3
[0049] A high thermal conductivity polyurethane potting compound is prepared by the following method:
[0050] (1) Preparation of component A:
[0051] 100 parts by weight of castor oil (hydroxyl equivalent of 300, average hydroxyl functionality of 2.4), 5 parts of 1,3-propanediol, 15 parts of didecyl adipate, 0.01 parts of dibutyltin dilaurate, 0.05 parts of defoamer BYK1794, and 15 parts of mesophase pitch-based foamed carbon powder (particle size of 200 mesh) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 100°C and dehydrated and degassed under vacuum for 3 hours to obtain component A.
[0052] (2) Preparation of component B:
[0053] 100 parts by weight of diphenylmethane diisocyanate (MDI-50) and 10 parts by weight of polypropylene glycol (molecular weight 400, hydroxyl value 5 mmol / g) were added to the reaction vessel and stirred until homogeneous. The mixture was then heated to 50°C and reacted for 4 hours before degassing to obtain component B.
[0054] (3) Preparation of high thermal conductivity polyurethane potting compound:
[0055] During potting, component A and component B are mixed evenly at a mass ratio of 4:1 and cured at 80°C for 6 hours to obtain the high thermal conductivity polyurethane potting compound.
[0056] Example 4
[0057] A high thermal conductivity polyurethane potting compound is prepared by the following method:
[0058] (1) Preparation of component A:
[0059] 80 parts by weight of hydroxyl-terminated polybutadiene (molecular weight 2750, hydroxyl value 0.75 mmol / g), 12.5 parts of 1,4-butanediol, 12.5 parts of dimethyl adipate, 0.01 parts of dibutyltin dilaurate, 0.015 parts of organosilicon defoamer BYK 066N, and 28.5 parts of amino-functionalized mesophase pitch-based foamed carbon powder were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 90°C and dehydrated and degassed under vacuum for 5 hours to obtain component A.
[0060] The amino-functionalized mesophase pitch-based foamed carbon powder is prepared by the following method: Mesophase pitch-based foamed carbon powder (particle size 200 mesh) is added to a mixed solution of ethanol and water with a volume ratio of 2:1 and dispersed evenly. Then, 20 wt% of tetraethyl orthosilicate of the mesophase pitch-based foamed carbon powder is added. Under stirring, hydrochloric acid is added dropwise until the pH of the solution is 4. After stirring and reacting at 30°C for 1 hour, ammonia water with a weight of 3 times that of the mesophase pitch-based foamed carbon powder and 40 wt% of 3-aminopropyltriethoxysilane of the mesophase pitch-based foamed carbon powder are added. The stirring and reaction are continued for 12 hours. After centrifugation, the precipitate is washed with water and ethanol in sequence and dried under vacuum to obtain the amino-functionalized mesophase pitch-based foamed carbon powder.
[0061] (2) Preparation of component B:
[0062] 90 parts by weight of diphenylmethane diisocyanate (MDI-50) and 10 parts by weight of hydroxyl-terminated polybutadiene (molecular weight 2750, hydroxyl value 0.75mmol / g) were added to a reaction vessel and stirred until homogeneous. The mixture was then heated to 40°C and reacted for 5 hours before degassing to obtain component B.
[0063] (3) Preparation of high thermal conductivity polyurethane potting compound:
[0064] During potting, component A and component B are mixed evenly at a mass ratio of 3:1 and cured at 60°C for 6-12 hours to obtain the high thermal conductivity polyurethane potting compound.
[0065] The tensile shear strength and thermal conductivity of the high thermal conductivity polyurethane potting compound obtained in the above embodiments were tested. The tensile shear strength was tested according to GB / T7124-2008 standard, and the thermal conductivity was tested according to ASTM D5470-2012 standard. The performance test results of the high thermal conductivity polyurethane potting compound obtained in the embodiments are shown in Table 1 below.
[0066] Table 1. Performance test results of high thermal conductivity polyurethane potting compounds obtained from different embodiments.
[0067]
[0068]
[0069] As can be seen from the table above, the addition of mesophase pitch-based foamed carbon powder significantly improves the thermal conductivity of the polyurethane potting compound. Furthermore, compared to simply adding mesophase pitch-based foamed carbon powder, the addition of amino-functionalized mesophase pitch-based foamed carbon powder can further improve the thermal conductivity of the polyurethane potting compound. At the same time, the polyurethane potting compound also exhibits high tensile shear strength, indicating high adhesion strength to the substrate. After aging under harsh conditions of 85℃ and 85%RH for 30 days, it still maintains its original level, demonstrating its high temperature and humidity resistance.
[0070] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A high thermal conductivity polyurethane potting compound, characterized in that, Includes component A and component B; wherein, Component A comprises the following raw materials in parts by weight: 60-100 parts of polyol, 5-15 parts of chain extender, 5-15 parts of plasticizer, 0.01-0.05 parts of catalyst, 0.01-0.05 parts of defoamer, and 15-30 parts of mesophase pitch-based foamed carbon powder. Component B comprises the following raw materials in parts by weight: 60-100 parts isocyanate and 10-25 parts polymer polyol; The particle size of the mesophase pitch-based foamed carbon powder is 100-300 mesh; The mesophase pitch-based foamed carbon powder is an amino-functionalized mesophase pitch-based foamed carbon powder. This amino-functionalized mesophase pitch-based foamed carbon powder is obtained by hydrolyzing mesophase pitch-based foamed carbon powder with tetraethyl orthosilicate to obtain a composite material of mesophase pitch-based foamed carbon / SiO2. After coupling the composite material of mesophase pitch-based foamed carbon / SiO2 with an aminosilane coupling agent, the amino-functionalized mesophase pitch-based foamed carbon powder is obtained. The aminosilane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, or 3-(2-aminoethylamino)propyltrimethoxysilane.
2. The high thermal conductivity polyurethane potting compound according to claim 1, characterized in that, The mass ratio of component A to component B is 1-4:
1.
3. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The polyol is a vegetable oil polyol and / or a polymer polyol.
4. The high thermal conductivity polyurethane potting compound according to claim 3, characterized in that, The vegetable oil polyol is at least one of castor oil, palm oil, or soybean oil; the polymer polyol is at least one of polypropylene glycol, polyglycerol, or hydroxyl-terminated polybutadiene.
5. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The chain extender is a small molecule diol.
6. The high thermal conductivity polyurethane potting compound according to claim 5, characterized in that, The small molecule diol is at least one of 1,4-butanediol, diethylene glycol, 1,3-propanediol, or neopentyl glycol.
7. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The plasticizer is at least one of dibutyl terephthalate, didecyl terephthalate, dimethyl adipate, or didecyl adipate.
8. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The catalyst is at least one of dibutyltin dilaurate, bismuth neodecanoate, or zinc neodecanoate.
9. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The defoamer is at least one of BYK1794, polymeric defoamer BYK1790, or silicone defoamer BYK 066N.
10. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The isocyanate is at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, or terephthalic diisocyanate.
11. The high thermal conductivity polyurethane potting compound according to claim 1 or 2, characterized in that, The polymer polyol is at least one of hydroxyl-terminated polybutadiene, polypropylene glycol, polycarbonate diol, poly(1,4-butanediol adipate) diol, or poly(ethylene adipate) diol.
12. A method for preparing a high thermal conductivity polyurethane potting compound, characterized in that, Includes the following steps: (1) Mix 60-100 parts of polyol, 5-15 parts of chain extender, 5-15 parts of plasticizer, 0.1-0.5 parts of catalyst, 0.01-0.05 parts of defoamer and 15-30 parts of mesophase pitch-based foamed carbon powder evenly by weight, and heat and dehydrate under vacuum to obtain component A; mix 60-100 parts of isocyanate and 10-25 parts of polymer polyol evenly by weight, and heat and react to obtain component B; (2) Mix component A and component B evenly, and heat to cure, to obtain the high thermal conductivity polyurethane potting compound; The particle size of the mesophase pitch-based foamed carbon powder is 100-300 mesh; The mesophase pitch-based foamed carbon powder is an amino-functionalized mesophase pitch-based foamed carbon powder. This amino-functionalized mesophase pitch-based foamed carbon powder is obtained by hydrolyzing mesophase pitch-based foamed carbon powder with tetraethyl orthosilicate to obtain a composite material of mesophase pitch-based foamed carbon / SiO2. After coupling the composite material of mesophase pitch-based foamed carbon / SiO2 with an aminosilane coupling agent, the amino-functionalized mesophase pitch-based foamed carbon powder is obtained. The aminosilane coupling agent is at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, or 3-(2-aminoethylamino)propyltrimethoxysilane.
13. The method for preparing the high thermal conductivity polyurethane potting compound according to claim 12, characterized in that, In step (1), the temperature for vacuum dehydration is 80-100℃ and the time is 3-8h, and the temperature for the reaction is 30-50℃ and the time is 4-9h; in step (2), the temperature for ripening is 40-80℃ and the time is 6-24h.
Citation Information
Patent Citations
Polyurethane heat-conducting insulating adhesive and preparation method thereof
CN112608708A
Polyurethane glue heat-conducting pouring sealant and preparation method thereof
CN114316882A
Heat-conducting flame-retardant polyurethane adhesive and preparation method thereof
CN115160972A
Heat-conducting polyurethane pouring sealant as well as preparation method and application thereof
CN115322734A
High-thermal-conductivity polyurethane, and preparation method and application thereof
CN115572363A